Investigation of blended learning video resources to teach health students clinical skills: An integrative review. (April 2018) - Coyne, Elisabeth; Rands, Hazel; Frommolt, Valda; Kain, Victoria; Plugge, Melanie; Mitchell, Marion
Abstract: Objectives: The aim of this review is to inform future educational strategies by synthesising research related to blended learning resources using simulation videos to teach clinical skills for health students. Design: An integrative review methodology was used to allow for the combination of diverse research methods to better understand the research topic. This review was guided by the framework described by Whittemore and Knafl (2005), Data Sources: Systematic search of the following databases was conducted in consultation with a librarian using the following databases: SCOPUS, MEDLINE, COCHRANE, PsycINFO databases. Keywords and MeSH terms: clinical skills, nursing, health, student, blended learning, video, simulation and teaching. Review Methods: Data extracted from the studies included author, year, aims, design, sample, skill taught, outcome measures and findings. After screening the articles, extracting project data and completing summary tables, critical appraisal of the projects was completed using the Mixed Methods Appraisal Tool (MMAT). Results: Ten articles met all the inclusion criteria and were included in this review. The MMAT scores varied from 50% to 100%. Thematic analysis was undertaken and we identified the following three themes: linking theory to practice, autonomy of learning and challenges of developing a blended learning model . Blended learning allowed for different student learning styles, repeated viewing, and enabled links between theory and practice. The video presentation needed to be realistic and culturally appropriate and this required both time and resources to create. Conclusions: A blended learning model, which incorporates video-assisted online resources, may be a useful tool to teach clinical skills to students of health including nursing. Blended learning not only increases students' knowledge and skills, but is often preferred by students due to its flexibility. Highlights: Blended learning using videos increases both knowledge and skills of nursing students. Blended learning caters to different student learning styles. Time and resources are required to ensure a realistic video representation.